Alternative Randomized Trial Designs in Surgery: A Systematic Review. Issue 5 (22nd November 2022) - Augustinus, Simone; van Goor, Iris W.J.M.; Berkhof, Johannes; Daamen, Lois A.; Groot Koerkamp, Bas; Mackay, Tara M.; Molenaar, I.Q; van Santvoort, Hjalmar C.; Verkooijen, Helena M.; van de Ven, Peter M.; Besselink, Marc G.
Abstract : Introduction: Randomized controlled trials (RCTs) yield the highest level of evidence but are notoriously difficult to perform in surgery. Surgical RCTs may be hampered by slow accrual, the surgical learning curve, and lack of financial support. Alternative RCT designs such as stepped-wedge randomized controlled trials (SW-RCTs), registry-based randomized controlled trials (RB-RCTs), and trials-within-cohorts (TwiCs) may overcome several of these difficulties. This review provides an overview of alternative RCT designs used in surgical research. Methods: We systematically searched PubMed, EMBASE, and Cochrane Central for surgical SW-RCTs, RB-RCTs, and TwiCs. A surgical RCT was defined as a randomized trial that studied interventions in patients undergoing general surgery, regardless of the affiliation of the corresponding author. Exponential regression analysis was performed to assess time trends. Results: Overall, 41 surgical RCTs using alternative designs were identified, including 17 published final RCT reports and 24 published protocols of ongoing RCTs. These included 25 SW-RCTs (61%), 13 RB-RCTs (32%), and 3 TwiCs (7%). Most of these RCTs were performed in Europe (63%) and within gastrointestinal/oncological surgery (41%). The total number of RCTs using alternative designs exponentially increased over the last 7 years ( P <0.01), with 95% (n=39/41) of the total number published within this time frame. The most reported reasons for using alternative RCT designs were avoidance of contamination for SW-RCTs and generalizability of the trial population for RB-RCTs and TwiCs. Conclusions: Alternative RCT designs are increasingly used in surgical research, mostly in Europe and within gastrointestinal/oncological surgery. When adequately used, these alternative designs may overcome several difficulties associated with surgical RCTs.